MRNA transport in fungal top models. (10th October 2017) - Niessing, Dierk; Jansen, Ralf‐Peter; Pohlmann, Thomas; Feldbrügge, Michael
Abstract : Eukaryotic cells rely on the precise determination of when and where proteins are synthesized. Spatiotemporal expression is supported by localization of mRNAs to specific subcellular sites and their subsequent local translation. This holds true for somatic cells as well as for oocytes and embryos. Most commonly, mRNA localization is achieved by active transport of the molecules along the actin or microtubule cytoskeleton. Key factors are molecular motors, adaptors, and RNA‐binding proteins that recognize defined sequences or structures in cargo mRNAs. A deep understanding of this process has been gained from research on fungal model systems such as Saccharomyces cerevisiae and Ustilago maydis . Recent highlights of these studies are the following: (1) synergistic binding of two RNA‐binding proteins is needed for high affinity recognition; (2) RNA sequences undergo profound structural rearrangements upon recognition; (3) mRNA transport is tightly linked to membrane trafficking; (4) mRNAs and ribosomes are transported on the cytoplasmic surface of endosomes; and (5) heteromeric protein complexes are, most likely, assembled co‐translationally during endosomal transport. Thus, the study of simple fungal model organisms provides valuable insights into fundamental mechanisms of mRNA transport boosting the understanding of similar events in higher eukaryotes. WIREs RNA 2018, 9:e1453. doi: 10.1002/wrna.1453 This article is categorized under: RNA Interactions with Proteins and Other Molecules > Protein–RNA Recognition RNA Interactions with Proteins and Other Molecules > RNA–Protein Complexes RNA Export and Localization > RNA Localization Abstract : Eukaryotic microorganisms like Saccharomyces cerevisiae (left) and Ustilago maydis (right) serve as role models to study actin‐ or microtubule‐dependent mRNA transport, respectively.